Treatment of Patients With Atrial Fibrillation and Heart Failure With Reduced Ejection Fraction. Issue 16 (18th April 2017) - Verma, Atul; Kalman, Jonathan M.; Callans, David J.
Abstract : Atrial fibrillation (AF) and heart failure with reduced ejection fraction (HFrEF) frequently coexist, and each complicates the course and treatment of the other. Recent population-based studies have demonstrated that the 2 conditions together increase the risk of stroke, heart failure hospitalization, and all-cause mortality, especially soon after the clinical onset of AF. Guideline-directed pharmacological therapy for HFrEF is important; however, although there are various treatment modalities for AF, there is no clear consensus on how best to treat AF with concomitant HFrEF. This in-depth review discusses the available data for the treatment of AF in the setting of HFrEF, focuses on areas where more investigation is necessary, examines the clinical implications of randomized and observational clinical trials, and presents suggestions for individualized treatment strategies for specific patient groups.